Salt stress-induced protein pattern associated with photosynthetic parameters and andrographolide content in Andrographis paniculata Nees. Issue 1 (2nd January 2015) - Talei, Daryush; Valdiani, Alireza; Maziah, Mahmood; Sagineedu, Sreenivasa Rao; Abiri, Rambod
Abstract: Andrographis paniculata is a multifunctional medicinal plant and a potent source of bioactive compounds. Impact of environmental stresses such as salinity on protein diversification, as well as the consequent changes in the photosynthetic parameters and andrographolide content (AG) of the herb, has not yet been thoroughly investigated. The present study showed that the salinity affects the protein pattern, and subsequently, it decreased the photosynthetic parameters, protein content, total dry weight, and total crude extract. Exceptionally, the AG content was increased ( p ≤ 0.01). Moreover, it was noticed that the salinity at 12 dS m −1 led to the maximum increase in AG content in all accessions. Interestingly, the leaf protein analysis revealed that the two polymorphic protein bands as low- and medium-sized of 17 and 45 kDa acted as the activator agents for the photosynthetic parameters and AG content. Protein sequencing and proteomic analysis can be conducted based on the present findings in the future. Graphical abstract: : Impact of salinity on the protein pattern, photosynthetic parameters and andrographolide content in Andrographis paniculata Nees.